Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
The Henry Luis Watkins home built by he and his sons after they tore down the original log cabin Albert Watkins and Pauline Gibson Shoemaker in the front yard